Myths from Beauty Myths: A Critical Review of Naomi Wolf's Thoughts - Salman Al Farisiy (al-Afkar, Journal For Islamic Studies, 2024)
This paper examines more deeply Naomi Wolf's thoughts on beauty. According to him, universal and physically dependent beauty standards are a myth that oppresses women. Two things that underlie the existence of beauty myths are the motifs and elements that form them. The first motive for the formation of myths was for women to become entangled in industrialization and consumerism. Furthermore, the motive for the existence of myths is for women to remain in a subordinated position. There are three elements that form myth, namely; culture, religion and sexuality. All three have the function of keeping women in a subordinated position. To get out of the myth, Naomi Wolf made an offer in the form of a personal construction of beauty. This article provides the finding that Naomi Wolf's reading and offerings regarding lesbianism, subordination, and nudity will lead women to new myths. Islam as a shumul (comprehensive) religion provides a comprehensive beauty construction that includes the intellectual, moral and spiritual beauty of women.